The effectiveness of Compassion-focused therapy on the level of self-care, self-worth, well-being and responsibility of women with breast cancer - Moradhasel , Afsaneh; Zakeripour , Gholamreaza; Malihialzackerini , Saied (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this research was to determine the effectiveness of compassion-focused treatment in self-care, self-worth, well-being and responsibility of women with breast cancer. Method: The current research is a semi-experimental type of research with a pre-test and post-test-follow-up plan with a control group and using the selection of subjects in the experimental and control groups. The statistical population of the present study was made up of all women with cancer referred to Boo Ali Hospital in the second half of 2018. According to the files filed in this hospital, their number is about 260 people. The sampling method was based on the Cochran P.Q formula. For this purpose, according to Cochran’s formula, 30 people were selected non-randomly as a statistical sample (15 people for each group). The research tools included the self-care questionnaire of Rigel et al. (2009), the self-esteem questionnaire of Crocker et al. (2003), the Ryff psychological well-being scale (1989), and the California accountability questionnaire (1987). Compassion-based therapy, strategies and techniques, as well as teaching tips, summarized from Gilbert (2014). This treatment was held in 12 sessions for 12 weeks and 1 session each week and each session lasted 60 minutes. The analysis method in this research was mixed. Results: The findings of the research showed that the treatment focused on compassion was effective in self-care, self-worth, well-being and responsibility of women with breast cancer (0.001) and these results have sufficient stability and maintain their effect in the long term. Conclusion: According to the findings of the research, it seems that one of the effective treatment approaches on the self-worth, well-being and responsibility of women with breast cancer is the use of treatment focused on compassion.